Measurement of morphological changes of pear leaves in airflow based on high-speed photography - Zhang, Chao; Zhou, Hongping; Xu, Linyun; Ru, Yu; Ju, Hao; Chen, Qing (Frontiers in Plant Science, 2022)
The morphological changes of leaves under the airflow have a significant effect on the deposition of pesticide droplets on the leaves, but the wind-induced vibration of the leaves is complicated to measure. In this study, an aerodynamic test of the pear leaf was conducted in the wind tunnel, and binocular high-speed photography was used to record the deformation and vibration of the leaves under various airflow velocities. Experiments showed that air velocity (v) had a significant effect on the morphological response of the leaf. As v increased, the leaf was in three states, including static deformation, low-frequency vibration, and reconfiguration of airfoil steady state. The mutation from one state to another occurred at the critical velocity of vcr1 and vcr2. By tracking the leaf marker point, various morphological parameters were calculated, including the bending angle of the petiole, the wind deflection angle, and the twist angle of leaves under different air velocities. When vcr1<= v <=vcr2, the parameters changed periodically. When v< vcr1, the petiole and the leaf bent statically, and the bending angle of the petiole and the wind deflection angle of the leaf gradually increased. When v >vcr2, the morphology of the leaf and the petiole was stable. Besides, this study tracked and measured the wind deflection area of leaf, which was consistent with the theoretical calculation results. The measurement of the leaf morphological parameters can reflect the morphological changes of leaves under airflow, thus providing a basis for the decision-making of air-assisted spray airflow.